The National Oesophagogastric Cancer Awareness Campaign: a locality outcome analysis from County Durham. Issue 4 (24th February 2017) - Koo, Sara; Awadelkarim, Bidour; Dhar, Anjan
Abstract : Introduction: Oesophageal and gastric cancer is common. Despite advances in investigation and treatment, the outcomes from these cancers remain poor. As part of the Be Clear On Cancer Campaign, the Department of Health runs the National Oesophagogastric Cancer Campaign each year, with key messages of (1) 'Having heartburn most days, for 3 weeks or more could be a sign of cancer' and (2) 'if food is sticking when you swallow, tell your doctor'. Methods: We evaluated the effect of the National Oesophagogastric Cancer Campaign in our locality. Results: Reviewing new referrals from primary care for upper gastrointestinal symptoms during the campaign period, and a period thereafter, we found that there was no significant impact of the campaign in the diagnosis of oesophagogastric cancers. Furthermore, it increased routine waiting times for elective gastroscopies in our endoscopy units. Conclusion: We believe that alternative strategies need to be considered for earlier detection of oesophagogastric cancer.